Economic Community of West African States, Regional security and the Implementation of Humanitarian Intervention and the Responsibility to Protect: Rhetoric or Reality?. Issue 2 (July 2019) - Arthur, Peter
The last 25 years have seen Economic Community of West African States, through the use of various norms, structures and protocols, make the promotion of security and the implementation of humanitarian intervention and the responsibility to protect (R2P) important aspects of the political landscape in the sub-region. The article argues that despite the great strides made by the Economic Community of West African States (ECOWAS) in the implementation of R2P, there are not only challenges (inadequate funds available for peace and security missions, conflicting interests and lack of agreement, poor co-ordination, inadequate human and logistics capacity) with its application in the sub-region, but also concerns about its future. Thus, to promote security and realise the goals of implementing humanitarian intervention and R2P in the ECOWAS sub-region, not only should the actors involved have the requisite capacity but also political will and commitment, citizen awareness, and co-operation among ECOWAS member-states and with the international community should remain crucial to the process.